Brisbane City Council's Q100 assessment: How climate risk management becomes scientised. (December 2015) - Tangney, Peter
Abstract: This paper provides a report of climate risk management for the city of Brisbane between 1976 and 2011. Using the evidence presented by the Commission of Inquiry established to investigate extreme flooding events across Queensland in 2010–2011, this paper describes Brisbane City Council's ongoing attempts to derive a 'Q100' flood risk management metric as a means to determine urban planning policy. The evidence presented by the Commission demonstrates how the normative decisions that underpinned the Council's derivation of Q100 and which sought to maximise urban development in the Brisbane River floodplain were in direct conflict with State government's concurrent priorities relating to water resources supply and flood risk management. This account of conflicting climate risk management strategies by local and state government demonstrates how the derivation of technical expert evidence can become politicised to align with conflicting priorities, and are then used in a 'scientised' environmental planning process.